Exploration of Malaysian english as a second language pre-service teachers’ teaching practices in conducting drama activities as student-centred approach: a self-study / Faizah Jaafar - Jaafar, Faizah (2020)
Implementing a student-centred approach (SCA) in teaching is one of the underlying principles of the teaching curriculum in Malaysia. When teachers adopt SCA in school, they are implementing quality teaching according to guidelines from the Ministry of Education. However, studies on SCA indicated that Malaysian teachers’ practices contradict with the suggested SCA approach. Instead it was found that they adopted a teacher-centred approach (TCA). To ensure quality teaching takes place in the Malaysian English language classroom, pre-service teachers need to be exposed to quality teaching using a student-centred approach during their teacher training. Through self-study, the aim of this study is to explore the teaching practices of six pre-service TESL teachers in teaching English using drama activities to primary ESL Malaysian students during phase II practicum and whether their use of SCA practices contribute to quality teaching. It is assumed that the six pre-service teachers will adopt the SCA as exposure and experience were provided during their training. This study also enables myself as a researcher and teacher trainer to explore my own practices in teaching drama as a SCA teaching strategy to pre-service teachers. This study employed self-study research, a form of practitioner research done by teacher educators. Data were collected through semi-structured interviews, non-participant observations, and document analysis which include reflections and lesson plans. The finding reveals that the Malaysian pre-service TESL teachers adopted TCA in their teaching. Although some characteristics of SCA were observed in their practice but teachers assumed total control of the teaching and learning process thus making it predominately teacher-centered. The pre-sevice TESL teachers revealed that the challenges they faced; students’ low English proficiency level, time constraint, students’ age, classroom management skills and passive activities hindered them from implementing SCA. In addition, it was found that the beliefs that they formed during teacher training prevented them from implementing SCA even though SCA was emphasized. This study has brought about some practical implications. This self-study changed the way the researcher viewed herself as a teacher educator. The experience in implemention of this self-study research will change the way the researcher approach courses she will teach in the future. She will integrate beliefs in the learning process of the pre-service teachers and make them aware of their own beliefs about student-centred approach. Furthermore, when teacher educators conduct self-study and critical reflections, it contributes to the transformation of preservice teachers’ thinking about the implementation of the student-centred approach in teaching resulting in benefits for improvement of the English language proficiency of students.